13C abundance, water-soluble and microbial biomass carbon as potential indicators of soil organic carbon dynamics in subtropical forests at different successional stages and subject to different nitrogen loads - Fang, Hua-Jun; Yu, Gui-Rui; Cheng, Shu-Lan; Mo, Jiang-Ming; Yan, Jun-Hua; Li, Shenggong (Plant and soil, 2009)
Chronic atmospheric nitrogen deposition affects the cycling of carbon (C) and nitrogen (N) in forest ecosystems, and thereby alters the stable C isotopic abundance of plant and soil. Three successional stages, disturbed, rehabilitated and mature forests were studied for their responses to different nitrogen input levels. N-addition manipulative experiments were conducted at low, medium and high N levels. To study the responses of C cycling to N addition, the C concentration and 13 C natural abundances for leaf, litter and soil were measured. Labile organic carbon fractions in mineral soils were measured to quantify the dynamics of soil organic C (SOC). Results showed that three-year continuous N addition did not significantly increase foliar C and N concentration, but decreased C/N ratio and enriched 13 C in N-rich forests. In addition, N addition significantly decreased microbial biomass C, and increased water soluble organic C in surface soils of N-rich forests. This study suggests that N addition enhances the water consumption per unit C assimilation of dominant plant species, restricts SOC turnover in N-poor forests at early and medium successional stages (thus favored SOC sequestration), and vice versa for N-rich mature forests.